HARMONIZATION CHALLENGES OF IFRS WITH NATIONAL ACCOUNTING SYSTEMS - Zunnunov Lazizkhon Olimkhon ogli (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract. The harmonization of International Financial Reporting Standards (IFRS) with national accounting systems is a critical component of global economic integration. Researchers argue that IFRS improves transparency, comparability, and investor trust [3]. However, several methodological and institutional barriers hinder full adoption, especially in developing countries [2].